An annotated checklist of the chondrichthyan fishes inhabiting the northern Gulf of Mexico Part 1: Batoidea - Jones, Christian M.; Driggers, William B. Iii; Hannan, Kristin M.; Hoffmayer, Eric R.; Jones, Lisa M.; Raredon, Sandra J. (Zootaxa, 2020)
Herein we consolidate the information available concerning the biodiversity of batoid fishes in the northern Gulf of Mexico, including nearly 70 years of survey data collected by the National Marine Fisheries Service, Mississippi Laboratories and their predecessors. We document 41 species proposed to occur in the northern Gulf of Mexico. However, the validity of several of these reports and their associated data is questioned. In addition, we provide information and remarks concerning the distribution, conservation status, taxonomy and recorded history for each species covered.